DESAIN DAN IMPLEMENTASI SISTEM PEMANTAUAN KUALITAS UDARA DALAM RUANGAN BERBASIS ARDUINO - Raja Amelia Lestari; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2025)
In this research, a prototype is designed to detect indoor air quality. The designed system will display indoor air quality data on an LCD screen and provide a warning via a buzzer if the air quality reaches an unhealthy threshold. The LED indicator will light up as a visual indication of the air quality based on the concentration of detected pollutants, such as dust particles, harmful gases, temperature, and humidity. The MQ-135 sensor is used to detect harmful gases such as carbon dioxide that can affect air quality. The GP2Y1010AU0F sensor is used to detect particles, while the DHT22 is used to measure temperature and humidity. In the final stage, conclusions will be drawn based on the results of the system tests that have been carried out. It is hoped that through this research, the developed system can provide solutions to indoor air quality problems and contribute to creating a healthier environment for residents.